Nanocomposites: Step‐by‐Step Strategy for Constructing Multilayer Structured Coatings toward High‐Efficiency Electromagnetic Interference Shielding (Adv. Mater. Interfaces 5/2016). Issue 5 (7th March 2016) - Zou, Lihua; Zhang, Songlin; Li, Xiangpeng; Lan, Chuntao; Qiu, Yiping; Ma, Ying
Abstract : Y. Ma and co‐workers have utilized a simple and versatile step‐by‐step strategy to construct multilayer structured coatings for high‐efficiency electromagnetic interference (EMI) shielding in article number 1500476. The obtained graphite oxide/polypyrrole (GO/PPy) coating with a multilayer structure retains the softness, flexibility and sponginess of fabric materials, and endows the fabrics with excellent shielding effectiveness, fast thermal dissipation, and desirable stability. The step‐by‐step method realizes the control of EMI shielding and exhibits the advantages of nanostructure in EMI shielding, providing a new strategy for the design of high‐performance shielding materials.